Penerapan Model Role Playing (Bermain Peran) Untuk Meningkatkan Pemahaman Materi Penjumlahan Dan Pengurangan Bilangan Pada Kelas III - Siti Aminatus Zahro; Ribut Prastiwi Sriwijayanti; Didit Yulian Kasdriyanto (CV. ITTC INDONESIA, 2023)
Mathematics is an important subject to be taught at MI because mathematics is very useful in students' daily lives, especially in terms of subtraction and addition. However, not all students understand mathematics learning. Like the problems that occurred in Class III MI Nurul Hikmah students in their third year, they found difficulties in learning mathematics in the discussion of addition and subtraction. This is due to the lack of precise application of the learning method used. As educators must be more creative in utilizing learning methods. For this reason, researchers are very interested in carrying out this research by applying the Role Playing learning method to fix these problems and increase student scores. This research was carried out with the type of Classroom Action Research (CAR). With the stages of data collection using several ways, namely: observation, interviews, tests of discussion results, documentation, performance indicators. The process of data analysis with descriptive qualitative research. The results of research using the Role Playing method experienced a significant increase with the acquisition of the first cycle completeness value of only 32.5% and the second cycle reached 100%.